Kondisi Sosial Ekonomi dan Tingkat Kesejahteran Rumah Tangga Nelayan Skala Kecil di Desa Seraya Timur - Christofan, Teofilus; Negara, I Ketut Wija; Pratiwi, Made Ayu (Current Trends in Aquatic Science, 2025)
Fishermen are the main livelihood of the people in Seraya Timur Village, Karangasem, Bali. This study aimed to determine the socio-economic condition and prosperity of fishermen as measured by 10 indicators including the condition of health services, family education, transportation facilities, sense of security, social access, household income, household expenses, house condition/ownership, household facilities, and health conditions of household members. The research was conducted from April to July 2023 in East Seraya Village with a total of 43 respondents. All respondents answered the same question on a scale of one to three, then the weighted scores were totaled and all averaged to produce three categories, namely prosperous, moderate and less prosperous. The educational background of fishermen in the east is mostly elementary school, with an average income of Rp. 3,000,000 per month. Based on the criteria, the social conditions of respondents are good. Likewise, the economic conditions of fishermen's households are in good condition. The welfare level of fishing households in East Seraya Village is 91%, the category ranges between 2.42-3.12 in the prosperous category and the remaining 9% are in the welfare category 1.71-2.41 in the medium category.